The relationship between leadership - members exchange and organisational commitment in Saudi Arabia healthcare sector - Salem Ali, Algathia; Ali, Salem; Abdullah, Abdul Rashid; Mohamed, Rosmah; Yee, Choy Leong (ASR Research India, 2022)
The relationship between leadership - members exchange and organisational commitment has caught attention from human resource management and organisational behaviour scholars in recent years. According to recent management and psychological science literature, leadership is a term with several characteristics and a wide range of applications. This analysis aims to examine the impact of leadership - member exchange types on employee organisational commitment in Saudi Arabia's healthcare sector. This research focuses on the importance of self-enhancement as a mediating factor in the partnership between leadership - participant sharing and organisational engagement. This study employs a theoretically built model To observe and describe the interaction between variables. As a result, the leadership - members exchange theory and the Social Identity Theory is used in this analysis to address the relationship as mentioned earlier. Theoretical and observational experiments have been analysed and summarised in this paper to further investigate the connection. The thesis comes to a close with a drawback and a suggestion for potential studies.